Effectiveness of the Alexander Technique on the Static and Dynamic Balance of Young Men With Upper Crossed Syndrome - Hamid Babaei; Mohammad Hosein Alizadeh; Houman Minoonezhad; Azin Movahed (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Studies show that individuals with upper crossed syndrome have poor balance compared to healthy people for various reasons, including displacement of their center of gravity toward forward. This study aimed to evaluate the effectiveness of the Alexander technique on the static and dynamic balance of young men with the upper crossed syndrome.Methods In this quasi-experimental study, 24 subjects were purposefully selected and assigned to the experimental and control groups. The static and dynamic balance of the subjects were assessed by the Sharpened Romberg and timed up and go tests. The experimental group underwent 12 sessions of Alexander technique training during 6 weeks in individual and group sessions. The duration of individual sessions was 40, and that of group sessions was 60 minutes. The control group did not receive any training. During the training sessions, the subjects were taught the Alexander technique via manual guidance, as well as tactile, verbal, visual, and proprioception feedback. After collecting data, the data were analyzed using the analysis of covariance (ANCOVA) and paired sample t test. Results The study's final results showed a significant difference (P<0.001) between the experimental and control groups in the static balance after the Alexander technique intervention. Also, there was a significant difference (P<0.001) between the experimental and control groups in the dynamic balance after the Alexander technique intervention. Conclusion Based on the findings, the Alexander technique had high effectiveness on the static and dynamic balance and improved the balance of the subjects. Considering the importance of balance in health and improving daily activities, the researchers suggested that health and rehabilitation professionals can apply the Alexander technique as a psychophysical re-education method to improve balance in people with upper crossed syndrome.